I always think it's forever : a love story set in Paris as told by an unreliable but earnest narrator - Goodman, Timothy (Simon Element, 2023)
The renowned graphic artist presents a memoir of a year abroad in Paris and how it led to an all-consuming love affair and eventual heartbreak that forced him to confront his own past traumas and toxic masculinity.